Transplanted human thymus slices induce and support T‐cell development in mice after cryopreservation. Issue 4 (1st February 2018) - Ross, Susan; Cheung, Melissa; Lau, Ching‐In; Sebire, Neil; Burch, Michael; Kilbride, Peter; Fuller, Barry; Morris, G. John; Davies, E Graham; Crompton, Tessa
Abstract : Nude mouse human thymus transplant model: Fresh or cryopreserved and thawed human thymus slices were transplanted subcutaneously into recipient nude mice. Nude mice subsequently produced mouse CD3 + CD4 + T‐cells.